2020
DOI: 10.1016/j.fct.2020.111809
|View full text |Cite|
|
Sign up to set email alerts
|

Toxic metal exposure as a possible risk factor for COVID-19 and other respiratory infectious diseases

Abstract: Multiple medical, lifestyle, and environmental conditions, including smoking and particulate pollution, have been considered as risk factors for CO rona VI rus D isease 2019 (COVID-19) susceptibility and severity. Taking into account the high level of toxic metals in both particulate matter (PM2.5) and tobacco smoke, the objective of this review is to discuss recent data on the role of heavy metal exposure in development of respiratory dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 213 publications
(212 reference statements)
1
45
0
7
Order By: Relevance
“…Some researchers have postulated that exposure to incense sticks (Amoatey et al 2020 ), pesticides (Rajak et al 2021 ), and heavy metals (Skalny et al 2020 ) may increase risk of Covid 19 morbidity and mortality. It has been hypothesized that pesticides exposure may increase risk of Covid 19 by damaging the respiratory, immune, cardiovascular, hepatic, and nervous systems (Rajak et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have postulated that exposure to incense sticks (Amoatey et al 2020 ), pesticides (Rajak et al 2021 ), and heavy metals (Skalny et al 2020 ) may increase risk of Covid 19 morbidity and mortality. It has been hypothesized that pesticides exposure may increase risk of Covid 19 by damaging the respiratory, immune, cardiovascular, hepatic, and nervous systems (Rajak et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been hypothesized that pesticides exposure may increase risk of Covid 19 by damaging the respiratory, immune, cardiovascular, hepatic, and nervous systems (Rajak et al 2021 ). Many toxic heavy metals can damage the immune system, and human and animal studies have reported that toxic heavy metal exposure can increase risk of respiratory infections like respiratory syncytial virus (RSV) and influenza (Skalny et al 2020 ). Some researchers have suggested that indoor incense exposure may increase Covid 19 risks (Amoatey et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“… Calder, 2020 Calder et al, 2020 Celik et al, 2021 Chaturvedi et al, 2004 Culbertson and Culotta, 2021 de Almeida Brasiel, 2020 de Jesus and de Araú jo Andrade, 2020 Ersö z and Y ı lmaz, 2021 Grzywa-Celiń ska et al, 2020 Hultman and Pollard, 2015 Moghaddam et al, 2020 Muhammad et al, 2021 Rahman and Idid, 2021 Skalny et al, 2020 Vogel-Gonzá lez et al, 2021 Zeng et al, 2021 .…”
Section: Uncited Referencementioning
confidence: 99%
“…The metal is nephrotoxic and may induce various health disorders, such as damage to bones (osteoporosis), kidney tubules, the brain, and the testis [ 9 , 10 , 11 ]. It has also been suggested that Cd is involved in metabolic diseases and susceptibility to respiratory tract infections [ 12 , 13 ]. A Cd intake of 23.2 μg/day (less than half the safe intake, according to current guidelines) might increase the risk of chronic kidney disease, mortality from heart disease, cancer at any site, and Alzheimer’s disease [ 14 ].…”
Section: Introductionmentioning
confidence: 99%